Pengaruh Ukuran Perusahaan, Struktur Modal, Likuiditas Dan Kepemilikan Institusional Terhadap Profitabilitas - Sri Suratmi Aji Pangesti; Kartika Hendra Titisari; Riana Rachmawati Dewi (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
A company has the same goal, namely to obtain large profits as a business entity. Companies must be able to manage their finances properly to ensure business continuity. Profitability is an important factor for a company. Food and beverage companies remain afloat in the midst of the COVID-19. Because some these products are the basic needs of people throughout Indonesia. The aim of this study is to investigate and analyze the effect of company size, capital structure, liquidity and institutional ownership on profitability. The data used in this study are quantitative data and secondary data in the form of financial statements. The population under study is the sub-sectors of the food and beverage industry listed on the Indonesian Stock Exchange (IDX) for the period 2016-2020. The sampling technique used was a purposeful sampling method with the number of samples meeting the criteria as many as 11 companies. The data analysis technique used is multiple linear regression analysis. The results of research and testing can conclude that company size and institutional ownership have no effect.